A preparation method of PVC processing aid

The PVC processing additive for long-chain/epoxy/siloxane structures is constructed through transesterification-copolymerization-crosslinking, which solves the problem that the improvement of PVC thermal stability performance affects processing fluidity and impact strength in the prior art, and achieves the improvement of thermal stability and mechanical properties of PVC materials.

CN119751767AInactive Publication Date: 2025-04-04SHANDONG RIKE CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510271843.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While improving thermal stability, existing PVC processing additives affect the mechanical properties of PVC processing fluidity and impact strength.

Method used

The PVC processing aids for long-chain/epoxy/siloxane structures are constructed through transesterification-copolymerization-crosslinking to enhance compatibility with PVC, improve mechanical properties, and capture the HCl generated by thermal degradation of PVC through the epoxy structure to block autocatalytic degradation.

Benefits of technology

The thermal stability and mechanical properties of PVC materials have been improved, and the comprehensive performance of PVC products has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of processing aids, and in particular to a method for preparing a PVC processing aid, comprising: S1, adding ricinoleic acid, epoxy soybean oil fatty acid methyl ester, and a catalyst to a reactor for mixing, and heating the reactor for reaction under a nitrogen atmosphere; S2, separating and obtaining an intermediate; S3, charging the high-pressure reactor with liquid CO2 and adjusting it to a supercritical state; S4, dissolving the intermediate, glycidyl methacrylate, an initiator, and a cosolvent in supercritical CO2 to form a copolymer; S5, gradient pressure relief to normal pressure, adding vinyl trimethoxysilane and a titanate catalyst, and continuing the reaction; S6, cooling and separating to obtain a cross-linked product; S7, using a bio-based solvent to dissolve the cross-linked product, removing impurities through an ultrafiltration membrane, and then spray drying to obtain a PVC processing aid. The intermediate and glycidyl methacrylate undergo free radical copolymerization to form a copolymer containing epoxy side chains, which can capture HCl generated by PVC degradation and improve thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of processing aids, and particularly relates to a method for preparing a PVC processing aid. Background Art

[0002] PVC processing aids are special additives used to improve the processing performance of PVC materials. Pure PVC resin is easy to decompose, has poor fluidity, low impact strength, and poor weather resistance during processing. The use of processing aids can effectively solve these problems. They can improve the processing performance of PVC, such as fluidity and plasticization speed, and can also improve the quality of the products.

[0003] Due to the chemical structure of PVC itself, its decomposition temperature is close to the processing temperature, which will cause PVC to decompose and produce hydrogen chloride during processing, and cause a chain reaction of autocatalytic decomposition, ultimately reducing the mechanical properties.

[0004] The existing technology usually adds stabilizers to improve the thermal stability of PVC, but the addition of stabilizers will reduce the processing fluidity of PVC, so it is necessary to add additives such as lubricants and synergists. Although the addition of a large amount of additives can improve the thermal stability of PVC to a certain extent, it will affect the mechanical properties of PVC such as impact strength. Summary of the invention

[0005] In view of the problems existing in the existing PVC processing aids, the present invention proposes a preparation method of PVC processing aids, aiming to improve the thermal stability of PVC materials and improve the quality of products, so as to achieve multiple effects with one dose and improve the comprehensive performance of PVC products. The specific implementation is through the following technical solutions: A method for preparing a PVC processing aid comprises the following steps: S1. Add 150-200 parts of ricinoleic acid, 200-250 parts of epoxidized soybean oil fatty acid methyl ester, and 3-5 parts of a catalyst to a reactor, mix, heat to 90-100° C. under a nitrogen atmosphere, and react for 3-3.5 hours; S2, after the reaction is completed, the temperature is cooled to room temperature, and the intermediate containing an ester bond is separated; S3, filling the autoclave with 80-120L of liquid CO2, adjusting the temperature and pressure to make the CO2 reach a supercritical state; S4, dissolving the intermediate, glycidyl methacrylate, initiator and co-solvent in supercritical CO2 at a mass ratio of 100: (25-35): (0.5-1): (8-15), reacting for 2-2.5 hours to obtain a copolymer; S5, after the reaction is completed, the pressure is gradually released to normal pressure, and 10% to 15% of vinyl trimethoxy silane, 2.5% to 3% of deionized water, and 0.3% to 0.5% of titanate catalyst are added to the copolymer system at a mass of 80 to 85°C for 1.5 to 2h. S6, after the reaction is completed, the mixture is cooled to room temperature and the cross-linked product is separated and obtained; S7. Dissolve the cross-linked product using 300 to 350 parts of a bio-based solvent to form a homogeneous solution, remove residual oligomers through an ultrafiltration membrane, and obtain a PVC processing aid by spray drying.

[0006] Preferably, the epoxy soybean oil fatty acid methyl ester is added in batches, with 70% of the total mass being added for the first time and the remaining 30% being added after 2 hours of reaction.

[0007] Preferably, the initiator is azobisisobutyronitrile.

[0008] Preferably, the co-solvent is ethanol.

[0009] Preferably, the azobisisobutyronitrile is added in three batches at intervals according to a proportion, the first addition amount of the azobisisobutyronitrile accounts for 35% of the total mass, and is added together with glycidyl methacrylate, intermediates and co-solvents; 50 minutes after the first addition, the second addition amount of the azobisisobutyronitrile accounts for 40% of the total mass, is dissolved in additional ethanol at a mass ratio of 1:1.2, and is injected through a high-pressure injection pump; 30 to 40 minutes after the second addition, the third addition amount of the azobisisobutyronitrile accounts for 25% of the total mass, is dissolved in additional ethanol at a mass ratio of 1:1.2, and is injected through a high-pressure injection pump.

[0010] Preferably, the catalyst is magnetic Fe3O4@IL-ZnO.

[0011] Preferably, the titanate catalyst is tetrabutyl titanate.

[0012] Preferably, the bio-based solvent is limonene.

[0013] Preferably, in step S5, CO2 released during the pressure relief process is condensed and recovered.

[0014] After adopting the above technical solution, the beneficial effects of the present invention are: This method constructs a long-chain / epoxy / siloxane structure through ester exchange-copolymerization-crosslinking. The long-chain structure enhances compatibility with PVC and improves mechanical properties. The intermediate undergoes a free radical copolymerization reaction with glycidyl methacrylate to form a copolymer containing epoxy side chains, which can capture HCl generated by PVC degradation and improve thermal stability. DETAILED DESCRIPTION

[0015] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the following specific embodiments will further describe the present invention in detail. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0016] Example 1 S1: Transesterification reaction to construct intermediates Prepare a nitrogen-protected reactor, add 200 parts of epoxidized soybean oil fatty acid methyl ester, 150 parts of ricinoleic acid and 3 parts of Fe3O4@IL-ZnO (Fe3O4 core surface loaded with ZnO, then coated with ionic liquid) as catalysts according to their mass proportions, start the stirring device at a rate of 300 rpm, mix the reactants evenly, and heat to 90°C at a rate of 5°C / min. React for 3 to 3.5 hours to generate long-chain intermediates containing ester bonds.

[0017] When adding epoxidized soybean oil fatty acid methyl ester, it needs to be added in batches. The first addition amount is 70% of the total mass to reduce the viscosity of the initial reaction system, and the remaining 30% is added after 2 hours of reaction. After the addition, the temperature is briefly lowered to 80°C, the current temperature is maintained, and the stirring rate is briefly increased from 300rpm to 500rpm for 10 minutes. After the end, the temperature is raised to the original temperature again to ensure uniform dispersion of the raw materials and avoid local overheating caused by the reaction.

[0018] The IL in the catalyst is an ionic liquid [BMIM][PF6], with a ZnO loading of 15wt% and a Fe3O4 particle size of 18nm. The alkaline site of ZnO promotes the deprotonation of the hydroxyl group of ricinoleic acid to generate oxygen anions, which attack the ester group of epoxy soybean oil fatty acid methyl ester, triggering an ester exchange reaction to generate new ester bonds. The hydrophobicity of [BMIM][PF6] can reduce ZnO leaching, improve the stability of the catalyst, and prevent particle agglomeration through electrostatic action, increasing the specific surface area of ​​ZnO and the exposure of active sites. The Fe3O4 core gives the catalyst superparamagnetism, and the catalyst can be quickly recovered through an external magnetic field, reducing catalyst loss.

[0019] Fourier transform infrared spectroscopy was used to determine the progress of the reaction. In the early stage (after 30 minutes of reaction), samples were taken twice at an interval of 10 minutes to verify whether the reaction was initiated. In the later stage (after 2.5 hours of reaction), samples were taken once every 15 minutes to capture the end point of the reaction. 5 to 10 μL of the reaction solution was applied to a KBr salt sheet (magnetic separation or centrifugation was required to avoid catalyst interference), and a Fourier transform infrared spectrometer was used to scan 4000 to 400 cm -1 Range, observe the changes of characteristic peaks: Hydroxyl peak (3400cm -1 ) gradually weakens as the reaction progresses, indicating that hydroxyl groups participate in the reaction to form ester bonds; Ester peak (1740 cm -1 ) is enhanced or stabilized, indicating that a new ester bond is formed or the reaction is basically completed.

[0020] The hydroxyl peak intensity dropped to the baseline level and the ester peak intensity stabilized, which was used as the criterion for judging the reaction endpoint.

[0021] S2: Separation and purification of intermediates After the reaction is completed, the temperature is cooled to room temperature. The Fe3O4 core in the catalyst has superparamagnetism and is rapidly magnetized under an external magnetic field of 0.5T, leaving the suspended state and concentrating at the bottom of the reaction liquid to achieve solid-liquid separation. The catalyst is removed and the intermediate is retained by membrane separation technology based on the molecular weight difference between the intermediate and the unreacted monomer, impurities, and by-products.

[0022] S3: Construction of supercritical CO2 system A high-pressure reactor with a sapphire window was selected and filled with 80L of liquid CO2 with a purity of ≥99.9%. The temperature was raised to 35°C at a rate of 2°C / min and the pressure was increased to 8MPa to make the CO2 reach the critical point.

[0023] S4: Free radical graft copolymerization The intermediate, glycidyl methacrylate, azobisisobutyronitrile and ethanol were mixed uniformly in a mass ratio of 100:25:0.5:8, and the mixed solution was injected into a high-pressure reactor through a high-pressure injection pump to dissolve it in supercritical CO2. The stirring rate was maintained at 400 rpm, and the temperature was raised to 65°C at 5°C / min. The reaction was carried out for 2 to 2.5 hours to obtain a copolymer.

[0024] Ethanol is used as a co-solvent to reduce the polarity of supercritical CO2, inhibit the self-polymerization of glycidyl methacrylate, and improve the solubility of glycidyl methacrylate in the supercritical CO2 system. Azobisisobutyronitrile is used as an initiator, which decomposes to generate isobutyronitrile free radicals during the reaction. This free radical preferentially attacks the ester bond on the main chain of the intermediate to form a main chain macromolecular free radical, which then triggers the methacrylate group of glycidyl methacrylate to undergo free radical polymerization, ultimately forming a graft copolymer. Supercritical CO2 is used as a green solvent to reduce the viscosity of the system, promote monomer diffusion and free radical reaction efficiency.

[0025] Azobisisobutyronitrile was added in three batches: The first addition amount accounts for 35% of the total mass, which is used to quickly initiate the generation of main chain free radicals and start the grafting reaction, and is added together with glycidyl methacrylate, intermediates and ethanol; After 50 minutes, the second addition is 40% of the total mass, which is used to replenish the free radicals consumed by chain termination and maintain the chain growth rate. It is mixed with ethanol (additional addition) at a mass ratio of 1:1.2 and injected through a high-pressure injection pump; The third addition is made 30 to 40 minutes after the second addition, with an addition amount of 25% of the total mass, to prolong the activity in the late stage of polymerization and reduce the residual unreacted monomers. It is mixed with ethanol (additional addition) at a mass ratio of 1:1.2 and injected through a high-pressure injection pump.

[0026] By using the sapphire window of the high-pressure reactor and in-situ detection by Fourier transform infrared spectroscopy, the characteristic peak changes in the reaction system can be monitored in real time to achieve non-invasive endpoint judgment. When the ester peak intensity tends to be stable, it indicates that the main chain grafting reaction is completed.

[0027] S5: Silane crosslinking modification After the reaction is finished, the pressure is gradually reduced to normal pressure. The pressure is reduced from 8MPa to 5MPa at a rate of 0.8MPa / min, from 5MPa to 2MPa at a rate of 0.5MPa / min, and from 2MPa to normal pressure at a rate of 0.2MPa / min. The CO2 released during the pressure reduction process is condensed and recovered, and then recycled after molecular sieve dehydration.

[0028] Add 10% vinyl trimethoxysilane by weight of the copolymer system, 2.5% deionized water by weight of the copolymer system, and 0.3% tetrabutyl titanate by weight of the copolymer system, maintain a stirring rate of 300 rpm, and heat to 80°C at 5°C / min for 1.5 to 2 hours. Si-OCH3 in vinyl trimethoxysilane is hydrolyzed to form Si-OH, which reacts with the hydroxyl groups in the copolymer to form a Si-OC cross-linked network. Tetrabutyl titanate activates Si-OCH3 by coordination, accelerates the condensation reaction, and inhibits side reactions, ensuring that the reaction proceeds in the direction of forming a Si-OC cross-linked network.

[0029] Using the sapphire window of the high-pressure reactor, the Fourier transform infrared spectroscopy in situ detection can monitor the characteristic peak changes in the reaction system in real time to achieve non-invasive endpoint judgment. Si-OC characteristic peak (1100cm -1 ) continued to increase until it stabilized, and the methoxy peak (1080cm -1 ) intensity dropped to the baseline, indicating that cross-linking was complete.

[0030] S6: Post-processing and purification After the reaction is finished, the temperature is lowered to room temperature. A circulating cross-flow mode is adopted to intercept the cross-linked product using membrane separation technology.

[0031] S7: Purification of functionalized end products 300 parts of bio-based solvent limonene were used to dissolve the cross-linked product to form a homogeneous solution, and the residual oligomers were removed by ultrafiltration membrane. The PVC processing aid was prepared by spray drying.

[0032] Steps S1, S4, and S5: take samples every 20 minutes or observe the characteristic peak of the epoxy group (850 cm -1 ) once and observe the intensity change. If the real-time peak area is 90% I O ≤I t <95%I O (decay rate 5-10%), 0.8-1.5 parts of borate ester should be added to the reaction system as an epoxy stabilizer (decay rate 5-8%, add 0.8-1 parts of borate ester, decay rate 8-10%, add 1-1.5 parts of borate ester) to inhibit its ring opening. t <90%I O (decay rate > 10%), the reaction needs to be terminated immediately.

[0033] Example 2 S1 adjustment: 250 parts of epoxidized soybean oil fatty acid methyl ester, 200 parts of ricinoleic acid, 5 parts of Fe3O4@IL-ZnO, heat to 100°C to obtain an intermediate.

[0034] S3 adjustment: Fill in 120L of liquid CO2 with a purity ≥99.9% to make CO2 reach the critical point.

[0035] S4 adjustment: the intermediate, glycidyl methacrylate, azobisisobutyronitrile and ethanol are uniformly mixed in a mass ratio of 100:35:1:15, and the temperature is raised to 70° C. to obtain a copolymer.

[0036] S5 adjustment: 15% vinyltrimethoxysilane, 3% deionized water and 0.5% tetrabutyl titanate, heated to 85° C. to prepare a cross-linked product.

[0037] S7 adjustment: 350 parts of bio-based solvent limonene are used to dissolve the cross-linked product to form a homogeneous solution, and the residual oligomers are removed by ultrafiltration membrane. The PVC processing aid is obtained by spray drying.

[0038] Example 3 S1 adjustment: 220 parts of epoxidized soybean oil fatty acid methyl ester, 180 parts of ricinoleic acid, 3.5 parts of Fe3O4@IL-ZnO, heat to 100°C to obtain an intermediate.

[0039] S3 adjustment: Fill in 100L of liquid CO2 with a purity ≥99.9% to make the CO2 reach the critical point.

[0040] S4 adjustment: the intermediate, glycidyl methacrylate, azobisisobutyronitrile and ethanol are uniformly mixed in a mass ratio of 100:30:0.8:10, and the temperature is raised to 70° C. to obtain a copolymer.

[0041] S5 adjustment: 12% vinyltrimethoxysilane, 2.8% deionized water and 0.35% tetrabutyl titanate, heated to 85° C. to prepare a cross-linked product.

[0042] S7 adjustment: 330 parts of bio-based solvent limonene are used to dissolve the cross-linked product to form a homogeneous solution, and the residual oligomers are removed by ultrafiltration membrane. The PVC processing aid is obtained by spray drying.

[0043] The PVC resin and PVC processing aid are heated to 120°C in a high-speed mixer in proportion. After hot mixing, the materials need to be transferred to a cold mixer, cooled to 45°C for standby use, and extruded through a twin-screw extruder to obtain a PVC sample.

[0044] The addition amount of the PVC processing aid prepared by the method of Example 1 is 5% and 10%, respectively, and the prepared PVC samples are recorded as PVC01-05 and PVC01-10. The addition amount of the PVC processing aid prepared by the method of Example 2 is 5% and 10%, respectively, and the prepared PVC samples are recorded as PVC02-05 and PVC02-10. The addition amount of the PVC processing aid prepared by the method of Example 3 is 5% and 10%, respectively, and the prepared PVC samples are recorded as PVC03-05 and PVC03-10. Dioctyl phthalate additives (general-purpose DOP) are selected as comparative example 1, and the addition amounts are 5% and 10%, respectively, and the prepared PVC samples are recorded as PVC-A05 and PVC-A10. Epoxidized soybean oil additives (epoxy fatty acid butyl ester) are selected as comparative example 2, and the addition amounts are 5% and 10%, respectively, and the prepared PVC samples are recorded as PVC-B05 and PVC-B10. A polyester additive (glyceryl polyester) was selected as comparative example 3, and the addition amounts were 5% and 10%, respectively. The prepared PVC samples were recorded as PVC-C05 and PVC-C10, respectively.

[0045] The tensile strength test was carried out according to the ASTM D638 standard, and the elongation at break was obtained simultaneously. The PVC sample was heated at a heating rate of 10°C / min in a nitrogen atmosphere using a thermogravimetric analyzer (TGA) to determine the 5% mass loss temperature (T5%). According to the ISO 177:2016 standard, the PVC sample was placed in an environment of 70°C for accelerated aging for 240 hours, and then its mass loss rate was measured. The performance test results of the PVC sample are shown in Table 1.

[0046]

[0047] Table 1. PVC processing aid performance test results As can be seen from Table 1, the PVC processing aid prepared in the present application has stronger thermal stability and tensile strength, which can make the PVC material tougher and more durable, while improving the stability of the PVC material in a high temperature environment, preventing or slowing down material degradation or performance degradation caused by high temperature.

[0048] This method constructs a long-chain / epoxy / siloxane structure through ester exchange-copolymerization-crosslinking. The long-chain structure enhances the compatibility with PVC and improves the mechanical properties. The epoxy structure captures HCl produced by thermal degradation of PVC to generate chlorohydrins, blocking the autocatalytic degradation of PVC to achieve multiple effects with one dose, bringing significant performance improvements to PVC products.

[0049] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to specific embodiments. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PVC processing aid, characterized in that: The steps include: S1. Add 150-200 parts of ricinoleic acid, 200-250 parts of epoxidized soybean oil fatty acid methyl ester, and 3-5 parts of a catalyst to a reactor, mix, heat to 90-100° C. under a nitrogen atmosphere, and react for 3-3.5 hours; S2, after the reaction is completed, the temperature is cooled to room temperature, and the intermediate containing an ester bond is separated; S3, filling the autoclave with 80-120L of liquid CO2, adjusting the temperature and pressure to make the CO2 reach a supercritical state; S4, dissolving the intermediate, glycidyl methacrylate, initiator and co-solvent in supercritical CO2 at a mass ratio of 100: (25-35): (0.5-1): (8-15), heating to 65-70°C, reacting for 2-2.5 hours, and obtaining a copolymer; S5, after the reaction is completed, the pressure is gradually released to normal pressure, and 10% to 15% of vinyl trimethoxy silane, 2.5% to 3% of deionized water, and 0.3% to 0.5% of titanate catalyst are added to the copolymer system at a mass of 80 to 85°C for 1.5 to 2h. S6, after the reaction is completed, the mixture is cooled to room temperature and the cross-linked product is separated and obtained; S7. Dissolve the cross-linked product using 300 to 350 parts of a bio-based solvent to form a homogeneous solution, remove residual oligomers through an ultrafiltration membrane, and obtain a PVC processing aid by spray drying.

2. The method for preparing a PVC processing aid according to claim 1, characterized in that: The epoxy soybean oil fatty acid methyl ester was added in batches, with 70% of the total mass added for the first time and the remaining 30% added after the reaction lasted for 1.5 hours.

3. The method for preparing a PVC processing aid according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.

4. The method for preparing a PVC processing aid according to claim 3, characterized in that: The co-solvent is ethanol.

5. The method for preparing a PVC processing aid according to claim 4, characterized in that: The azobisisobutyronitrile is added in three batches at intervals according to a proportion, the first addition amount of the azobisisobutyronitrile accounts for 35% of the total mass, and is added together with the intermediate, glycidyl methacrylate and the co-solvent; 50 minutes after the first addition, the second addition amount of the azobisisobutyronitrile accounts for 40% of the total mass, is dissolved in additional ethanol at a mass ratio of 1:1.2, and is injected through a high-pressure injection pump; 30 to 40 minutes after the second addition, the third addition amount of the azobisisobutyronitrile accounts for 25% of the total mass, is dissolved in additional ethanol at a mass ratio of 1:1.2, and is injected through a high-pressure injection pump.

6. The method for preparing a PVC processing aid according to claim 1, characterized in that: The catalyst is magnetic Fe3O4@IL-ZnO.

7. The method for preparing a PVC processing aid according to claim 1, characterized in that: The titanate catalyst is tetrabutyl titanate.

8. The method for preparing a PVC processing aid according to claim 1, characterized in that: The bio-based solvent is limonene.

9. The method for preparing a PVC processing aid according to claim 1, characterized in that: In step S5, CO2 released during the pressure relief process is condensed and recovered.

Citation Information

Patent Citations

  • Method for preparing plasticizer and lubricant by using semi-drying oil or drying oil

    CN101863768A

  • Preparation method and application of modified soybean oil plasticizer

    CN116444713A